Video-Assisted Simulation Training in Burn Management: A Comparative Cohort Study on the Assessment of Technical and Non-technical Competencies. Issue 8 (August 2021) - Gasteratos, Konstantinos; Paladino, Joseph Robert; Murray, W. Bosseau; Goverman, Jeremy
Highlights: Non-technical skills represent an emerging trend in contemporary clinical practice in burns and trauma. Non-technical skills include leadership, communication, situation awareness, decision making, and teamwork. These skills are pivotal in successfully managing a polytrauma patient with associated burn injuries. Both technical and non-technical skills are enhanced through burn simulation training based on video demonstrations. Abstract: Background: Written material remains one of the most common methods of education, however the current generation of learners may benefit from additional different media. In our study, we aim to quantify the effects of an innovative video instruction on subsequent resident performance in a burn patient simulation. Methods: Following IRB approval, 60 Plastic Surgery residents were randomly assigned to two groups. The control group ("non-video" group) (n = 30) was given only written material as preparation. The experimental group ("video" group) (n = 30) was provided access to video training materials in addition to the written material on technical and non-technical skills. Their videotaped performances on simulation were evaluated by a blinded surgical faculty member. The comparison of variables between the two groups was performed using a Mann-Whitney test for non-normal distributions of quantitative variables, and Fisher's Exact Probability test for qualitative data. Statistical significance was set at p < 0.05. Results: Compared to the non-video group, the video group achieved significantly higher scores in the technical skills of assessment of breathing (p = 0.015), disability (p = 0.023), and exposure (p = 0.005) and in the non-technical skills of decision-making (p = 0.035). Conclusions: In residents participating in burn patient simulations, video training in advance of the simulation significantly improved their assessments of breathing, disability, and exposure as well as decision-making. Our video is a valuable tool to enhance trainees' technical and non-technical competencies in managing burn patient simulations.